Pembuatan Biodiesel Dari Bahan Baku Cpo (Crude Palm Oil) Dengan Reaksi Transesterifikasi Menggunakan Kolom Sentrifugal Kontaktor (Variasi temperatur Dan Waktu Reaksi) - Erziza, Winny Noviami; Amri, Idral; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Transesterification reaction is a reaction between oils (triglycerides) with alcohol to produce fatty acid alkyl esters and glycerol as a byproduct. Biodiesel is obtained by reacting vegetable oils or fats with methanol. So that the resulting product is known as the methyl ester. Due to, production of petroleum fuels is limited, it is necessary to develop a vegetable oil to produce biodiesel. One of the vegetable oil that can be used is derived from CPO (Crude Palm Oil) by using a column centrifugal contactor. In this study, biodiesel obtained by transesterification of CPO (Crude Palm Oil), using KOH catalyst. The process is conducted by variation of temperature (50ºC., 60°C, and 70ºC), and reaction time (0.5, 1 and 1.5 hours), with a fixed variable stirring speed of 300 rpm and a molar ratio of methanol / oil 6: 1, the concentration of catalyst KOH 1%wt. Based on the test results showed that the transesterification reaction time and temperature affected by the speed of reaction formation of biodiesel. The good operating conditions obtained in this study at temperature of 60°C, and the reaction time of 1.5 hours which resulted in the conversion reaction of 39,47%. The percentage of ester product area is 6.37% and 28,894% glycerol. Methyl ester product was obtained in the form of palmitate, dimethyl azelate, methyl myristate, methyl laurate, and methyl nonanoat. Characteristics of biodiesel produced in this study meets to the Indonesian Standards of biodiesel, with the value of the kinematic viscosity (40°C) 3.91 to 4.15 cSt, Density (40ºC) = 872.95 to 886.44kg/m3, and a flash point at 136ºC (min. 100ºC).Keywords: Crude Palm Oil, transesterification, biodiesel, column centrifugal contactor